Effect of isometric upper-extremity exercises on the activation of core stabilizing muscles - Tarnanen, Sami P; Ylinen, Jari J; Siekkinen, Kirsti M; Mälkiä, Esko A; Kautiainen, Hannu J; Häkkinen, Arja H (Archives of physical medicine and rehabilitation, 2008)
To evaluate whether isometric exercises for the upper extremities could sufficiently activate core stabilizing muscles to increase muscle strength. Cross-sectional study. Department of physical medicine and rehabilitation at a Finnish hospital. Healthy adult women (N=20). Not applicable. Peak isometric strength of the back and abdominal muscles was measured and relative loading in 5 test exercises was evaluated by surface electromyography. The rectus abdominis and obliquus externus abdominis were activated to the greatest degree in a bilateral shoulder extension exercise and the average surface electromyographic activity was 114% and 101% compared with the amplitude elicited during the maximal isometric trunk flexion exercise. Horizontal shoulder extension elicited the greatest activation of the longissimus and multifidus muscles. In this exercise, the activity levels of the left side multifidus and longissimus muscles were 84% and 69%, respectively, compared with the level of activity elicited during trunk extension. Of all the exercises studied, bilaterally performed isometric shoulder extension and unilaterally performed horizontal shoulder extension elicited the greatest levels of activation of the trunk musculature. Thus, it can be assumed that these exercises elicit sufficient levels of contraction of the trunk muscles for the development of their endurance and strength characteristics in rehabilitation.